Transformasi Menuju Green Behavior: Peran Pelatihan, Keterampilan, dan Motivasi Dalam Mewujudkan Tenaga Kerja Berkelanjutan - Eddy Sabarudin (Keizai, 2025)
Environmentally-oriented training is expected to enhance participants’ green skills that are relevant to sustainable work practices. Furthermore, mastering green skills is expected to serve as a bridge toward environmentally friendly behavior change. This study uses a quantitative approach with a survey design targeting participants of vocational training programs. The aim is to examine the relationship between Green Training and Green Behavior, mediated by Green Skills and moderated by Motivation in the context of vocational education. Data were collected using a standardized questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample consisted of 138 respondents who had previously participated in environmentally focused training. The findings show that Green Training has a positive effect on the development of Green Skills, and Green Skills significantly contribute to changes in Green Behavior. The study also indicates that the effect of Green Training on Green Behavior is fully mediated by Green Skills, while Motivation does not significantly moderate the relationship between skills and behavior. This study contributes theoretically to the literature on environmentally based training and sustainable behavior, and provides practical implications for vocational training designers to place greater emphasis on developing applicable skills that directly influence participants’ behavior.